MO888QUALITY OF LIFE AND QUALITY OF SLEEP IN MAINTENANCE HEMODIALYSIS PATIENTS: REPORTS FROM TWO HEMODIALYSIS CENTERS IN IRAN. (29th May 2021) - Hashemi, Samaneh; Rezaee, Roya; Saeedi, AmirHossein; Hojati, Hazhir; Yahyavi Sahzabi, Reza; Maghsudi, Fatemeh
Abstract: Background and Aims: Patients with End Stage Kidney Disease (ESKD) usually tend to have lower Quality of Life (QoL) compared to the general population. The purpose of this study was to determine the QoL and quality of sleep in patients on maintenance hemodialysis (MHD) and its relation with medical factors. Method: This descriptive-analytical study was performed on 145 patients on MHD in two hospitals affiliated to Abadan University of Medical Sciences. Patients' QoL was assessed via KDQOL-SF questionnaire. For sleep quality, Pittsburgh Sleep Quality Questionnaire (PSQI) was used. Demographic information of patients, type of vascular access, history of dialysis, and frequency and duration of each dialysis session were collected. The average results of related laboratory tests in the last six months, were also recorded for each patient. Results: Of 145 MHD patients, 81 (55%) were men and 64 were women. Most patients (53%) were between 30 and 60 years old. Illiteracy was present in 48 (33%) patients. Unemployed patients accounted for 70% of patients (99) and most of the participants (83.44%) lived in the city. Of 145 patients, 102 (70.34%) were married, 20 (13.79%) were single, and the rest were widows. The mean dialysis adequacy of patients was 1.14, and 53% had dialysis adequacy less than 1.2. The average quality of life score was 66.00 ±13, suggesting a high QoL in this group of patients. literacy was significantly a ssociated with QoL score (P<0.001). Likewise, there was significant association between QoL score and income level (p <.001), the effect of Kidney disease on life (p <.001), working status (p <.009), social functioning (p <.046), and marital status (p <.001). The quality of social interactions was significantly associated with residence location (p <.001). On the other hand, the presence of Kidney disease burden, sexual dysfunction, unemployment, role emotional and role physical, was associated with low QoL scores. We found a significant relationship between hemoglobin level and cognitive function (p <.001, r= .075). In addition, significant relationships between phosphorus levels and physical function (p=.021) and role emotional (P:0.04) were observed. Seemingly, phosphorus levels were inversely related with sexual function in our patients (p <0.001, r= - .013). Our data also suggested that serum calcium levels may have an impact on the patients' social function (p=.038). The mean score of sleep quality was 7.00±4.00. Most of the patients (61%) had a PSQI>5, indicating a poor sleep quality. High sleep quality (PSQI<5) is significantly associated with low age and high-income level. There was also a significant relationship between the average sleep quality and general health (p <0.001, r= -0.206), social function (p= 0.018, r=-0.208), and energy fatigue (p <0.001, r= -0.309). Conclusion: Our study showed that a wide range of determinants, including demographic, socioeconomic and disease-related factors can significantly influence the QoL and sleep quality in ESKD patients undergoing hemodialysis. Among them, modifiable factors including laboratory test results, socioeconomic determinants and psychosocial status should be addressed and accordingly treated and solved. Hence, an improvement in both the QoL and sleep quality of maintenance hemodialysis patients will be expected. Keywords: Hemodialysis, Quality of life, Sleep quality, Sociodemographic characteristics.